Machine learning in sport - Robertson, S. (Human Performance Summit - Asia Pacific Summit, 2018)
The Human Performance Summit is designed to provide a forum for industry professionals who are working with human performance data on a daily basis to gain meaningful outcomes. For the Asia Pacific Summit we have a full two days of sessions from experts across elite sports and tactical human performance. Sports Sam Robertson, currently holding a joint appointment as the Victoria University-Western Bulldogs Head of Research and Innovation, gave a perceptive presentation into the realm of machine learning and it`s relationship with decision making in elite sports. Sam has a particular focus on the application of machine learning to sports problems and improving decision-making through analytics. In this presentation Sam explains how AI (artificial intelligence) can improve decision making in sport and decrease the factor of human error going into the future. Quick links to topics Sam covered: - Confusing domain expertise with decision-making expertise (7:39) - How can machine learning help? (9:46) - Framing the question appropriately (12:26) - Training Availability (13:48) - Team Selection (18:46) - How do we evaluate a decision? (22:27) - Bounded rationality (22:40) - AFL Specific Examples (30:16) - Interpreting Complexity in Game Play (39:50)